Color-tunable persistent luminescence hybrid materials via radiative energy transfer. Issue 15 (6th July 2022) - Zhao, Dan; Song, Lijun; Li, Jinlei; Lin, Fenglong; Wang, Shenglong; Wu, Yincai; Lin, Fulin
Abstract : Colorful, persistent luminescence materials are in great demand in many technological fields but their synthesis remains a challenge. Abstract : Colorful, persistent luminescence materials are in great demand in many technological fields but their synthesis remains a challenge. Herein, a unique strategy is reported, that is, a full spectrum adjustment of the persistent luminescence was achieved by using an organic polymer fluorescent dye (PFD) as an efficient light-conversion material. The observed emission spectra upon photoexcitation of these polymer films were assigned to dual emission bands: the fluorescence emission of the PFD and the phosphorescence emission of the phosphor. There is a balance point between the two emission bands, and thus we can precisely control the luminescence colors by adjusting the left and right luminous intensity. Moreover, phosphorescence emission colors of films can be tuned from blue, purple and green to red by varying the concentration of PFD and the type of phosphor. These emission lights were achieved through a radiative energy transfer pathway between light-conversion molecules and the phosphor. A possible mechanism of the light conversion process was proposed. The results presented here would offer a promising way to effectively and conveniently broaden the color of persistent luminescence, which may open up new opportunities for individual customization, colorful surface coating and anti-counterfeiting of polymers.